Increasing Growth and Yield of Upland Rice by Application of Vesicular Arbuscular Mycorrhizae and Potassium Fertilizer - Dedi Natawijaya (UNIVERSITY OF LAMPUNG, 2012)
Field experiment with a split plot design has been carried out in order to assess the growth characteristics and yields, and effectiveness of MVA upland rice which were given potassium fertilizer in two growing seasons. MVA inoculation consisted of three treatments (without MVA, Glomus sp. and Gigaspora sp.) while potassium fertilizer consisted of five levels (0, 12.5, 25, 37.5, and 50 kg ha-1 K). The results showed that plant growth variable which was inoculated by MVA at any levels of K fertilizer was higher in the dry season than that in the wet season, whereas the opposite occurred for net assimilation rate. Potassium content of leaf tissue, shoot/root ratio, and grain weight per hill was determined and mutually dependent on genus MVA, dosages of K fertilizer, and growing season. Harvest index and grain dry weight per hill were influenced by the growing season and the genus MVA but the effect did not depend on each other. At all dosages of K fertilizer and any MVA genera, Gigaspora sp. inoculation was better than that of Glomus sp. Dry weight of grains per hill was affected by the contribution of grain content per hill, weight of 1000 grains and number of productive seedlings per hill. The optimum dosage of K fertilizer in the dry season was 32.4 kg ha-1 K with grain yield 3.12 Mg ha-1 for inoculation of Gigaspora sp., whereas the optimum dosage in the wet season was 34.2 kg ha-1 K for the treatment Glomus sp. inoculation with Gigaspora sp. in the wet season did not reach dosages of optimum K fertilizer.